Sensitivity Analysis of Diabetes Mellitus and Tuberculosis for Confounders : A Comprehensive Systematic Review - Amelia, Gita; Suryanto, Joko (International Medical Journal Corp. Ltd, 2024)
Background: People with diabetes mellitus (DM) have a higher tuberculosis (TB) risk. Tuberculosis (TB) and diabetes mellitus (DM) are two diverse conditions of immense public health importance existing for centuries. TB was traditionally identified with poverty while DM was considered as an entity associated with prosperity. Methods: This systematic review focused on full-text English literature published between 2014 and 2024 using the PRISMA 2020 guidelines. Editorials and review pieces published in the same journal as the submission without a DOI were not accepted. The literature was compiled using PubMed, ScienceDirect, and SagePub, among other online venues. Result: Ten publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: Both DM and TB have been associated with significant morbidity and mortality from time immemorial.